A nearly cylindrically symmetric source in Brans–Dicke gravity as the generator of the rotational curves of the galaxies - dos Santos, S. Mittmann [UNESP]; da Silva, J. M. Hoff [UNESP]; Guimarães, M. E.X.; Neto, J. L. (Springer Nature, 2017)
Observation shows that the velocities of stars grow by approximately 2–3 orders of magnitude when the distances from the centers of the galaxies are in the range of 0.5–82.3 kpc, before they begin to tend to a constant value. Up to now, the reason for this behavior is still a matter for debate. In this work, we propose a model which adequately describes this unusual behavior using a (nearly) cylindrical symmetrical solution in the framework of a scalar–tensor-like (the Brans–Dicke model) theory of gravity.